Деякі аспекти виконання якісного наукового дослідження - Усова, Оксана; Сологуб, Олександр; Usova, O.; Solohub, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статті розглянуто проблему якості виконання наукових досліджень. Аналіз науково-методичної літератури виявив, що методології досліджень приділяється мало уваги, а оцінка їх носить суб’єктивний характер. Відмічено, що якість наукового дослідження залежить від дизайну, що забезпечує мінімальну кількість систематичних і випадкових помилок. The article deals with the problem of scientific research quality. Some aspects of the scientific research implementation are analyzed. Indicated that scientific research implementation involves intellectual and creative activities to explore certain subject with obtaining of new results. The scientific research process aimed at collecting objective and complete information. There are many methods for its statistical analysis, the choice of which depends on the type of data. The researcher must interpret, evaluate and analyze the results. Analysis of scientific and methodical literature found out that research methodology has received little attention, but their assessment is subjective. Emphasis on the importance of the methodology for determining the content, structure and quality of research was made. It is noted that the quality of research depends on its design, which provides minimal possibility of mistakes. For minimization of it meta-analysis can be applied. In the article attention to the need of the quality of scientific papers improvement was paid.
Some aspects of qualitative scientific research implementation
Keywords: наукові дослідження; scientific research; дизайн дослідження; методологія; якість дослідження; помилки; research design; methodology; research quality; mistakes